Case Report: Clinical Use of a Patient-Individual Magnetic Resonance Imaging-Based Stereotactic Navigation Device for Brain Biopsies in Three Dogs - Gutmann, Sarah; Flegel, Thomas; Müller, Marcel; Möbius, Robert; Matiasek, Kaspar; König, Florian; Winkler, Dirk; Grunert, Ronny (Frontiers in Veterinary Science, 2022)
Three-dimensional (3D) printing techniques for patient-individual medicine has found its way into veterinary neurosurgery. Because of the high accuracy of 3D printed specific neurosurgical navigation devices, it seems to be a safe and reliable option to use patient-individual constructions for sampling brain tissue. Due to the complexity and vulnerability of the brain a particularly precise and safe procedure is required. In a recent cadaver study a better accuracy for the 3D printed MRI-based patient individual stereotactic brain biopsy device for dogs is determined compared to the accuracies of other biopsy systems which are currently used in veterinary medicine. This case report describes the clinical use of this 3D printed MRI-based patient individual brain biopsy device for brain sampling in three dogs. The system was characterized by a simple handling. Furthermore, it was an effective and reliable tool to gain diagnostic brain biopsy samples in dogs with no significant side effects.